Ecocentric Friluftsliv in a Pedagogical Context: A Practical Approach to Ecophilosophy - E. Nerland, Jørgen; Henderson, Bob (The Trumpeter, 2025)
The ideas in ecophilosophy might appear as abstract concepts unless concretised. To remedy this, we suggest a practical approach to teaching ecophilosophy through the Scandinavian outdoor education tradition of friluftsliv. Our aim is to investigate how an outdoor education project concerning making firewood, from forest to fireplace or campfire, can convey concepts from predominantly the Norwegian ecophilosopher Sigmund Kvaløy Setreng to adult friluftsliv students. Our theoretical foundation shows that the ecocentric and pedagogical perspectives in friluftsliv have corresponding ideas to ecophilosophy in general. And a closer look at Setreng’s work in the field of ecophilosophy, with concepts such as “complexity versus complication,” “meaningful work,” and “organic time,” reveals practical dimensions applicable to friluftsliv. These dimensions are incorporated in the firewood project in an attempt to convey ecophilosophy to the students. Based on a description of the firewood project from the professor’s perspective, we analyse and explore in what way the experiential learning activities in this project convey selected ecophilosophical concepts. Our conclusion is that the firewood project to some extent indeed communicates important aspects. We thus argue that a practical approach like the one found in the firewood project can contribute to spreading the ideas of ecophilosophy.